Preparation and Characterization of Pt/TiO2 Nanotube Arrays (TNAs) Cathode by Photoreduction Method for Hydrogen Evolution - Ningsih, Sherly Kasuma Warda; Wibowo, Rahmat; Gunlazuardi, Jarnuzi (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
TiO2 nanotube arrays were fabricated using a two-step anodization method. TNAs have been modified by the photoreduction technique with Pt as the cathode in the photoelectrocatalytic zone for the reduction reaction of H+ to produce hydrogen. TNAs with Pt were modified using H2PtCl6 as the precursor by immersion of this solution on the TNA substrate. Pt/TNAs were characterized using SEM-EDX, UV-Vis DRS, XRD, Raman Spectroscopy, Photoluminescence (PL), and photoelectrochemical analysis. The results show that the morphology of TNAs in the tube forms 2.1mm in height, and Pt nanoparticles are formed on the mouth wall of the tube with a size of approximately 10nm. EDX analysis shows that the composition of Pt/TNAs is approximately 0.15%, Ti 37.09%, and O 62.76%, indicating that Pt has been decorated on the TNAs photoanode. The band gap of Pt/TNAs was 2.82 eV. The diffractogram shows three groups of diffraction peaks, indicating the presence of anatase TiO2, Ti as a substrate, and Pt, which has been modified in the TNAs. The Raman peaks of TNAs are confirmed to appear at Raman shifts of 144.75, 196.51, 395.94, 517.14, and 638.85 cm-1. PEC cathodes for hydrogen production using Pt-decorated TNAs have been successfully prepared using photoreduction.